Canopy temperature variability in a tropical rainforest, subtropical evergreen forest, and savanna forest in Southwest China - Song, Q-H; Zhang, Y-P; Sha, L-Q; Deng, X-B; Deng, Y; Wu, C-S; Lu, Z-Y; Chen, A-G; Zhang, S-B; Li, P-G; Zhou, W-J; Liu, Y-T (IForest (Viterbo), 2017)
Canopy temperature (Tc) measurements with infrared thermometry have been widely used to assess plant water status. Here, we evaluated Tc and its controlling factors in a primary tropical rainforest (TRF), subtropical evergreen broad-leaved forest (STF) and valley savanna forest (SAF) in southwestern China. We found differences between Tc and air temperature (Ta) of as much as 2.2 °C between the dry and wet seasons in the TRF. However, the canopy-to-air temperature difference (Tc-Ta) was only 0.3 °C between the dry and wet seasons in the STF. Solar radiation (SR) was the dominant factor in Tc-Ta variations during the dry and wet seasons at the three sites. The increased heating in the canopy leaves was likely the result of low stomatal conductance leading to low transpiration cooling. Changes in Tc-Ta in the TRF were highly sensitive to the degree of stomatal closure. The change in Tc-Ta was controlled by the climate, but inherent plant traits, such as stomatal conductance, also played an important controlling role.